2011
DOI: 10.1186/1423-0127-18-70
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone induces heart morphogenetic and functional defects by promoting the death of erythrocytes and the endocardium in zebrafish embryos

Abstract: Backgroundβ-Lapachone has antitumor and wound healing-promoting activities. To address the potential influences of various chemicals on heart development of zebrafish embryos, we previously treated zebrafish embryos with chemicals from a Sigma LOPAC1280™ library and found several chemicals including β-lapachone that affected heart morphogenesis. In this study, we further evaluated the effects of β-lapachone on zebrafish embryonic heart development.MethodsEmbryos were treated with β-lapachone or dimethyl sulfox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…To measure intestinal ROS production in zebrafish in vivo, zebrafish were incubated with CM-H2DCFDA (0.5 µg/mL, Thermofisher C6827, diluted in gnotobiotic medium) for 1 hr as indicated by previous studies (Wu et al, 2011). The zebrafish were then washed with GZM and imaged immediately using an stereofluorescence microcope (Leica M205 FA microscope equipped with a Leica DFC 365FX camera).…”
Section: Methodsmentioning
confidence: 99%
“…To measure intestinal ROS production in zebrafish in vivo, zebrafish were incubated with CM-H2DCFDA (0.5 µg/mL, Thermofisher C6827, diluted in gnotobiotic medium) for 1 hr as indicated by previous studies (Wu et al, 2011). The zebrafish were then washed with GZM and imaged immediately using an stereofluorescence microcope (Leica M205 FA microscope equipped with a Leica DFC 365FX camera).…”
Section: Methodsmentioning
confidence: 99%
“…All the experiments were performed in compliance with the approval of USC Institutional Animal Care and Use Committee (IACUC) protocol (Zebrafish IACUC Protocol number: 11767). These fish were maintained with filtered fresh water under 14 hours of incandescent light and 10 hours of dark conditions [20]. The fli1a promoter-driven enhanced green fluorescent protein (GFP) is expressed predominantly in vascular endothelial and endocardial cells.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of zebrafish blood was assumed to be similar to that of humans, and viscosity was estimated from the relative viscosity and particle volume fraction using literature data [2,24]. The obtained value, 7 centipoise (cP), was close to that of the trout (8cP) [20]. The density of blood was assumed to be similar to that of humans (1.06g/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was well established that during the developmental period, humans, rats, mice, and zebrafish exhibit heightened susceptibility to oxidative stress induced by excessive ROS production, which is implicated in the pathogenesis of CHDs . Several studies showed that ROS overproduction was integral and important in zebrafish cardiac malformations induced by PM 2.5 , trichloroethylene, β-lapachone, and benzo­(a)­pyrene. , High salt exposure also induced cardiac tube malformation during protozoan embryogenesis by producing excessive ROS . Numerous studies documented ROS overproduction induced by PM 2.5 exposure (Table S1).…”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%